Denitrogenative Hydrotrifluoromethylation of Benzaldehyde Hydrazones: Synthesis of (2,2,2‐Trifluoroethyl)arenes - Zhao, Zhensheng; Ma, Kevin C. Y.; Legault, Claude Y.; Murphy, Graham K. (Chemistry : a European journal, 2019)
Reacting hydrazones of arylaldehydes with Togni's CF 3 ‐benziodoxolone reagent, in the presence of potassium hydroxide and cesium fluoride, induces a denitrogenative hydrotrifluoromethylation event to produce (2,2,2‐trifluoroethyl)arenes. This novel reaction was tolerant to many electronically‐diverse functional groups and substitution patterns, as well as naphthyl‐ and heteroaryl‐derived substrates. Advantages of this process include the easy access to hydrazone precursors on a large scale, speed and operational simplicity, and being transition metal‐free.